Implementation of Muhammadiyah Organizational Management in Economic Empowerment in The Management of Sang Surya Mart Muhammadiyah Lempangan Branch, Gowa Regency - Supriyanto Supriyanto; Grace Christien Sumakul; Anwar Anwar (Institute of Computer Science (IOCS), 2023)
This study aims to determine the implementation of Muhammadiyah Organization management in economic empowerment in the management of Sang Surya Mart Muhammadiyah Lempangan, as well as find out the methods and factors that hinder and support Sang Surya Mart in improving the management of the Muhammadiyah Organization through the efforts of Sang Surya Mart. Qualitative research methods and types of research are descriptive. The data taken from Sang Surya Mart management can be collected by import, observation, interview, and documentation. The results of this study explain about Sang Surya Mart who is so active in the business field with the aim of restoring and carrying out the community's economy, in the development of the economy of the Muhammadiyah community is active in charging as well as actively trading by forming a store owned by Muhammadiyah. Even though in the development of human resources there are still obstacles that are influenced by the lack of capital and lack of buyers because goods are still limited and the population of Muhammadiyah is still minimal.